A United Nations General Assembly Special Session for mental, neurological, and substance use disorders: the time has come. - Judith K Bass; Thomas H Bornemann; Matthew Burkey; Sonia Chehil; Lenis Chen; John R M Copeland; William W Eaton; Vijay Ganju; Erin Hayward; Rebecca S Hock; Rubeena Kidwai; Kavitha Kolappa; et al. (PLoS Medicine, 2012)
Mental, neurological, and substance use (MNS) disorders are leading causes of the global burden of disease and profoundly impact the social and economic well-being of individuals and communities. The majority of people affected by MNS disorders globally do not have access to evidence-based interventions and many experience discrimination and abuses of their human rights. A United Nations General Assembly Special Session (UNGASS) is needed to focus global attention on MNS disorders as a core development issue requiring commitments to improve access to care, promote human rights, and strengthen the evidence on effective prevention and treatment.